2019
DOI: 10.21873/invivo.11747
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Gastrointestinal Cancer Detection by Nematode-NOSE (N-NOSE)

Abstract: Background/Aim: Early detection of gastrointestinal cancer may reduce mortality. Recently, Caenorhabditis elegans has been reported to be capable of differentiating patients with cancers from healthy persons by the smell of urine. This novel technique using C. elegans olfaction has been named as Nematode-NOSE (N-NOSE). Materials and Methods: We collected 180 urine samples from patients with gastrointestinal cancer and 76 samples from healthy subjects. N-NOSE test was performed using these samples and N-NOSE in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
0
23
1
Order By: Relevance
“…The first approach is to develop high-throughput and reproducible technology that can use the animal behavior preference itself as a diagnostic assay (e.g. the ‘N-nose’ demonstrated by Hirotsu et al, 2015 and Kusumoto et al, 2020) . Another possibility is to use the behavioral assay as an unbiased sensor system that could be coupled with a discovery method such as GC-MS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first approach is to develop high-throughput and reproducible technology that can use the animal behavior preference itself as a diagnostic assay (e.g. the ‘N-nose’ demonstrated by Hirotsu et al, 2015 and Kusumoto et al, 2020) . Another possibility is to use the behavioral assay as an unbiased sensor system that could be coupled with a discovery method such as GC-MS.…”
Section: Discussionmentioning
confidence: 99%
“… Hirotsu et al (2015) further showed that the C. elegans behavioral response worked strictly through G-protein coupled receptor (GPCR) mediated signaling and via chemosensory neurons known to be important for sensing VOCs. More recently and using a similar chemotaxis assay, a report by Kusumoto et al (2020) demonstrated that C. elegans accurately differentiates between matched preoperative and postoperative samples from patients that underwent gastrointestinal cancer resection. Thus, the natural behavioral response of C. elegans to cancer patient urine may provide a useful tool for detecting cancer VOCs at early, treatable stages or for monitoring residual disease.…”
Section: Introductionmentioning
confidence: 99%
“…The N-NOSE showed different behaviors before and after tumor removal via surgical operation, suggesting its usefulness as a highly sensitive method to monitor patients postoperatively [34]. The results were confirmed through the analysis of a relatively large study of 180 urine samples from patients with gastrointestinal cancer and 76 samples from healthy participants, indicating the method's high sensitivity as a gastrointestinal cancer screening test, with a significant value of 0.80 in the receiver operating characteristic analysis, even in early stage cancers [35].…”
Section: Caenorhabditis Elegans (C Elegans)mentioning
confidence: 66%
“…To utilize this system as a screening test for patients with early-stage PDAC, higher specificity is imperative. Despite the high specificity in previous studies [ 15 , 17 ], an excessive number of participants would need to be sent for detailed examination for PDAC. Moreover, the suitable urine dilution for early PDAC remains under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This biological diagnosis had a reported sensitivity of 95.8%, which was also acceptable even in patients in early-stage of cancer. Furthermore, reports have shown that this test demonstrated high sensitivity in cases of gastrointestinal cancers and negative changes in the postoperative period [ 16 , 17 ]. Moreover, this test could discriminate urine in a mouse model of pancreatic cancer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%